Effectiveness of Policy Implementation in Achievements of The Expected Food Pattern Score (Study in Kutai Kartanegara Regency, East Kalimantan) - Indarto, Kus (JPAS (Journal of Public Administration Studies), 2020)
The purpose of this study is to analyze the effectiveness of achievement policy implementation of Expectation Food Pattern Score in Kutai Kartanegara Regency. This research is a qualitative inquiry, and using descriptive method. The novelty of this study is analyzed expectation food pattern score for whole community, while previous studies analyzed children age 2-6 years. The data collected were analyzed using Interactive Model Analysis by Miles, Huberman and Saldana. The findings in the field show that the implementation of achievement policy implementation of Expectation Food Pattern Score in Kutai Kartanegara Regency has met the criteria of 5 right, namely: right policy, right implementer/actor, right target, right environment, and right proses. In other word, the implementation has been effective